Short communication: Importance of introgression for milk traits in the German Vorderwald and Hinterwald cattle - Hartwig, S.; Wellmann, R.; Emmerling, R.; Hamann, H.; Bennewitz, J. (Journal of dairy science, 2015)
The subject of the present study was to analyze the influence of genetic introgression on milk yield performance of the German local Vorderwald and Hinterwald cattle breeds. Deviations of milk yield, fat yield, and protein yield of cows as well as pedigree information were analyzed. A sire model was used to estimate genetic trend and effects of the migrant breeds. Migrant contributions to Vorderwald cattle were high and have been rising even in the recent past. The effects of these breeds on milk yield performance were positive. Montbéliarde cattle not only had the largest effect on milk production of Vorderwald cattle but also the highest genetic contribution to this breed. Genetic introgression with Montbéliarde continued until recently. This suggests that introgression of high-yielding breeds is still a preferred method for genetic improvement of local breeds, even though it diminishes their value for conservation. Hence, the current population management has too little focus on the preservation of genetic uniqueness. In comparison, migrant breed contributions to the Hinterwald cattle, a breed with a unique phenotype and an own niche, were moderate and almost constant over the time. For the Hinterwald cattle, no significant effect of migrant breeds could be detected, which suggests that population management has different priorities in different endangered breeds. We conclude that not only the registration of animals from local breeds but also the breeding programs themselves should be supported and need to be controlled.